Alien vascular plants in the Silesian Upland of Poland: distribution, patterns, impacts and threats - Tokarska-Guzik, Barbara; Węgrzynek, Beata; Urbisz, Alina; Urbisz, Andrzej; Nowak, Teresa; Bzdęga, Katarzyna (Biodiversity: Research and Conservation, 2011)
Symptoms of anthropogenic changes in the flora include processes of extinction in some species and spread in others. These tendencies have increased in magnitude in recent centuries, adversely affecting natural biodiversity on a regional, national and continental scale. The main idea behind the project presented here was to investigate the diversity of the alien vascular flora at the regional scale and to update the list of invasive alien species for the Silesian Upland. The aim of this study is also to provide a synthesis of the knowledge accumulated to date on the conditions for their occurrence, their distribution patterns and the possible threat they might pose. The distribution of particular species at the regional scale was investigated by mapping the species on a 2 km x 2 km grid. The study showed that the list of alien plant species for the Silesian Upland encompasses 338 species, including 125 archaeophytes, 195 kenophytes (=neophytes) and 18 species of an uncertain status in the Polish flora. A threat evaluation was performed for particular species on the basis of the number of localities, the diversity of preferred habitats recorded, and their current (over the last decade) tendency to colonise new localities. As a result, a final list of 101 invasive species has been selected. Among the alien plant species considered to be invasive in the area of the Silesian Upland, 20 species are identified as ‘weeds’ (13 archaeophytes and 7 kenophytes), another 25 (exclusively kenophytes), penetrating into natural habitats, are defined as ‘transformers’